Detection of latent tuberculosis infection in individuals before heart transplantation and heart transplant recipients - A. R. Sabirova; P. A. Fedotov; R. A. Sharipov; M. A. Simonenko; B. B. Musaeva; E. Yu. Vasilyeva; E. A. Stabrova; I. V. Kudryavtsev; D. A. Kudlay; A. A. Starshinova; D. M. Spelnikov (Translational Medicine, 2026)
Background. The effective functioning of the immune system in solid organ recipients against M. tuberculosis may be compromised due to the intensive action of immunosuppressive drugs. Identifying latent tuberculosis infection (LTBI) in patients on the heart transplant waiting list, as well as in heart transplant recipients, may help improve the epidemic situation. Objective. To determent the level of latent tuberculosis infection in patients before and after heart transplantation. Materials and Methods. A comparative prospective cohort study was conducted using immunodiagnostic data from individuals prior to heart transplantation ( n =14) and recipients of a transplanted heart ( n =28). The control group consisted of healthy individuals ( n =69) with no history of contact with TB patients. All participants underwent immunodiagnosis for tuberculosis infection. Results. Positive results were recorded significantly more frequently in recipients of a transplanted heart compared to the control group (53.6 % versus 4.4 %, p =0.001). In the pre-transplant patient group, the level of positive immunodiagnostic results was also significantly higher (35.7 %) than in the control group ( p =0.001). Despite this, there were no statistically significant differences between the recipient group and the transplant candidate group ( p =0.275). Conclusion. The LTBI rate in recipients of a transplanted heart (53.6 %) was determined to be 1.5 times more frequent compared to patients awaiting transplantation (35.7 %). Notably, both comparison groups demonstrated a significantly high level of LTBI relative to healthy individuals (4.4 %), which necessitates further examination of this patient cohort and investigation into the causes of these findings.